Portrait of MSMEs‘ Islamic Financial Literacy and The Impact on Business Development - Aqidah Asri Suwarsi; Aninta Gina Sharfina; Anisatun Anggraeni (Fakultas Agama Islam Universitas Muhammadiyah Yogyakarta, 2022)
MSMEs are part of the supporting aspects of the country's economy. However, the competitiveness of MSMEs in Indonesia towards the global economy still tends to be low when compared to other ASEAN countries. This is caused by low levels of education and expertise, difficulties in obtaining licensing for MSMEs, lack of access to capital, and lack of infrastructure support. One aspect that should not be missed from the field of education and expertise is the level of public financial literacy. The purpose of this study is not only to analyze and classify the level of financial literacy of MSMEs but also to examine the impact of literacy levels on the development of MSMEs. This research approach is descriptive quantitative with a sample size of 1392, obtained by using cluster random sampling technique in Special Region of Yogyakarta (DIY). The results of the study show that the financial literacy of MSMEs in DIY is Less Literate. The effect on the business developing had a positive and significant influence amounted to 36.1%. With this finding, it is expected to be an input for regulators in the framework of planning and implementing policies related to Islamic financial literacy.